Performance evaluation of multi carrier modulation techniques for HF frequency selective fading channel - Ahmad Sazmy Abd. Aziz, author; Ahmad Zuri Sha'ameri, author; National Conference on Telecommunication Technology (4th : 2003 : Shah Alam, Selangor) (Skudai : Universiti Teknologi Malaysia, 2003)
PSZJBL